Modified floating-zone crystal growth of Mg4Ta2O9 and its scintillation performance. Issue 20 (13th May 2020) - Yuan, Dongsheng; Moretti, Federico; Perrodin, Didier; Bizarri, Gregory; Shalapska, Tetiana; Dujardin, Christophe; Bourret, Edith
Abstract : Rods of single crystal MgTaO9 were produced free of macroscopic defects and their scintillation properties including afterglow were measured. The compound characteristics make it a candidate for high energy X-ray radiography applications. Abstract : Aiming to explore scintillator candidates for high-energy radiography, the environmentally friendly compound Mg4 Ta2 O9 was selected. Bulk crystals of good optical quality are needed to evaluate its scintillation performance against other commercial scintillators currently used such as CdWO4 and CsI:Tl. In this work, bulk single crystal rods of 3.5 mm in diameter with length up to 50 mm were obtained through optimization of the growth process. Particularly, the thermal gradients that impact the cooling of the crystal in the floating-zone furnace were modified. The scintillation properties of the produced Mg4 Ta2 O9 crystals, are reported. The scintillation decay and afterglow not reported previously have been measured. The afterglow results are compared to those of CdWO4, CsI:Tl and Y3 Al5 O12 :Ce. We confirmed a luminosity similar to that of CdWO4 .